The association between maternal renal function and pregnancy outcomes in type 1 and type 2 diabetes. (July 2020) - Seah, Jas-mine; Kam, Ning Mao; Wong, Lydia; Tanner, Cara; MacIsaac, Richard J.; Shub, Alexis; Ekinci, Elif I.; Houlihan, Christine
Abstract: Aims: To investigate the prognostic value of estimated glomerular filtration rate (eGFR) and albuminuria in determining pregnancy outcomes in women with type 1 and type 2 diabetes. Methods: An observational study of pregnant women with type 1 (n = 92) and type 2 diabetes (n = 106) who delivered between 2004 and 2014 at a single tertiary obstetric centre. Clinical and biochemical characteristics were determined and related to major obstetric outcomes: preeclampsia, preterm birth <32 and <37 weeks, and neonatal intensive care admission. We used univariate analyses and multivariable logistic regression models with eGFR using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation and albuminuria as covariates. Results: In the pooled diabetes cohort, multivariable logistic regression with eGFR and albuminuria status demonstrated that the presence of albuminuria (albumin-to-creatinine ratio ≥ 3.5 mg/mmol) (OR, 2.7; 95% CI, 1.42–4.99; P  = 0.002) was associated with preeclampsia, whilst an eGFR of < 120 mL/min/1.73 m 2 was associated with preterm birth < 32 weeks (OR, 1.04; 95% CI, 1.00–1.09; P  = 0.02). Conclusions: Despite its recognized limitations in pregnancy, lower eGFR values were associated with increased risk of adverse outcomes. Our exploratory data suggest eGFR, along with albuminuria, can aid in identifying women at high risk of developing adverse obstetric outcomes.